Mental Health Among Jail and Prison Inmates - Yi, Youngmin (Am J Mens Health, 2016)
Previous studies provide insight into the mental health of jail and prison inmates, but this research does not compare the two groups of inmates. Using data from the Fragile Families and Child Wellbeing Study, this article examines how the association between incarceration and self-reported mental health varies by facility type, net of an array of demographic and socioeconomic characteristics. Both jail and prison inmates report high rates of depression, life dissatisfaction, heavy drinking, and illicit drug use. In adjusted logistic regression models, those incarcerated in jails, compared with those not incarcerated, have higher odds of depression (odds ratio [OR] = 5.06, 90% confidence interval [CI; 1.96, 13.11]), life dissatisfaction (OR = 3.59, 90% CI [1.40, 9.24]), and recent illicit drug use (OR = 4.03, 90% CI [1.49, 10.58]). Those incarcerated in prisons have higher odds of life dissatisfaction (OR = 3.88, 90% CI [2.16, 6.94]) and lower odds of recent heavy drinking (OR = 0.32, 90% CI [0.13, 0.81]) compared with those not incarcerated. Furthermore, jail inmates report significantly more depression, heavy drinking, and illicit drug use than prison inmates. These results suggest the association between incarceration and mental health may vary substantially across facilities and highlight the importance of expanding research in this area beyond studies of prisons. The results also indicate that public health professionals in the correctional system should be especially attuned to the disproportionately high levels of poor mental health outcomes among jail inmates.